Renal infarction in a patient with thyrotoxicosis‐induced atrial fibrillation treated successfully with dabigatran, a case report and literature review - Anas Al‐sadi (17746794) (2022)
Renal infarction is an underdiagnosed condition with multiple possible causes, including atrial fibrillation. The treatment approach includes percutaneous endovascular therapy (PET) to restore blood flow, antiplatelet therapy, anticoagulation, or combination therapy, depending on the patient's status and available modalities. Warfarin is the standard anticoagulation therapy, although direct oral anticoagulation (DOAC) therapy is getting more popular. Here, we present a 60‐year‐old male patient with hyperthyroidism complicated by acute renal infarction, which was successfully treated with dabigatran, evident by non‐recurrence and restoration of blood flow in a follow‐up CT angiogram. This case report may open the door for the use of DOAC in acute renal infarction though more studies are needed to prove the efficacy. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.6693